Integrating Gender Issues in Community-Based Disaster Risk Management - World Bank (World Bank, Washington, DC, 2017)
This note on integrating gender issues in community-based disaster risk management is the fourth in a series of guidance notes on gender issues in dis-aster risk management (DRM) in East Asia and the Pacific. The first part of this note looks at reasons to adopt a gender sensitive approach for community based disaster risk management. The second part focuses on tools to support a gender conscious approach to community based DRM efforts. Community-based Disaster Risk Management (CBDRM) is an approach that seeks to actively engage at risk communities in the identification, analysis, implementation, monitoring and evaluation of disaster risks in order to reduce their vulnerabilities and enhance their capacities (ADPC 2004). The underlying rationale is that communities bearing the brunt of disasters have intimate knowledge of the issues and vulnerabilities they face and therefore, given appropriate support, are well-placed to identify solutions; plan and implement disaster risk reduction activities; and in the event of a disaster, manage relief and recovery efforts. The aim of disaster risk management is to reduce vulnerabilities and build the resilience of communities to external shocks of major hazard events. The CBDRM approach advocates equal community participation and involvement. It focuses on community vulnerabilities and is couched within the broader sustainable development and poverty reduction goals. Using a gender sensitive approach ensures that DRM is conducted in a comprehensive way, addressing the needs and harnessing the capacity of all people (women, girls, boys and men) living in the community. A gender sensitive CBDRM approach can have a positive impact on many aspects of women and men's lives. Working with existing women's networks helps strengthening women's participation in the community's decision-making processes. For example, women's participation can highlight issues related to gender-based violence and strengthen women's roles in community-based early warning systems. It can also be used to elevate the role of women as leaders who can drive a risk reduction agenda in support of community development goals.